Stereotypes about Romanians in education, professional orientation and in today's society - Elena Sestac (Association of Social and Educational Innovation, 2018)
Stereotypes and prejudices influence our daily lives, and in certain circumstances we operate with them, despite the fact that we think we are free of prejudices. Not infrequently, they can become barriers in the communication, knowledge and acceptance of those around us; from this point of view, we must have the readiness to deal with our own prejudices, so that we do not reach situations of discrimination, marginalization, rejection or exclusion of some people on subjective grounds, influenced by stereotypes and misrepresentations about others (we often observe that our attitude and behavior towards a stranger is influenced by the way that person looks or is dressed). This study is based on stereotypes. It aims to identify attitudes and behaviors that perpetuate or challenge gender stereotypes in education. We will see what is stereotype, prejudice, discrimination, we will go a little bit on gender, cultural and language stereotypes, and finally we will see concrete examples within a school unit. This theme has become a problem of society. Stereotypes give rise to prejudices, and further discrimination. And during this research I noticed that since we were born, these things have been instilled in us.